FACTORS CONTRIBUTING ONLINE GAMBLING AMONG UNIVERSITY STUDENTS IN BENGKULU CITY - Langcing; Agusalim; Antory Royan Adyan (Bengkoelen Justice : Jurnal Ilmu Hukum, 2025)
Online gambling has become an increasingly troubling phenomenon in society, particularly among university students. This study investigated the contributing factors and mitigation efforts related to online gambling crimes among university students in Bengkulu City. The research employed a qualitative methodology, utilising in-depth interviews and analysis to collect and examine data. The data sources for this study were university students in Bengkulu City who are directly involved in online gambling. Informants were selected using purposive sampling principles. The findings of this research indicate that there are numerous types of gambling websites on the internet. The initial exposure of students to online gambling often occurred through interactions with fellow students, whether on the same campus or living together with those already familiar with and involved in online gambling. Additionally, other factors contribute to their continued participation in online gambling. Keywords: Factors Contributing, Online Gambling, University Students